Visualization of Granblue Fantasy Game Traffic Pattern Using Deep Packet Inspection Method - Stiawan, Deris; Prabowo, Christian; Heryanto, Ahmad; Afifah, Nurul; Minarno, Agus Eko; Budiarto, Rahmat (Universitas Muhammadiyah Malang, 2020)
Granblue Fantasy is one of Role Playing Games (RPG). It’s a video role-playing game developed by Cygames. This research to observes the Granblue Fantasy Game. The purpose is to analyze the traffic data of the Granblue Fantasy to find the pattern using Deep Packet Inspection (DPI), Capturing the Data Traffic, Feature Extraction Process and Visualize the Pattern. The Pattern are Gacha, Solo Raid, Casino and Multiraid. This research demonstrate that Multiraid battle has more data than other pattern with TTL 237.